THE PERCEPTION OF THE ACADEMIC COMMUNITY OF LANGUAGE FACULTY TOWARDS THE CURRICULUM OF INDEPENDENT LEARNING-INDEPENDENT CAMPUS (MBKM) - hendar; Heri Heryono; Uning Kuraesin; Hety Nurohmah; Raden Novitasari (Universitas Widyatama, 2022)
This research is a descriptive qualitative on adaptation to independent learning independent campus (MBKM) into the curriculum of study programs, especially on the survey result of questionnaire shared by DIKTI to the whole elements at university. Adaptation focused on concept study program curriculum development model and activity program implementation MBKM. The curriculum development model includes the MBKM policy design in higher education institutions, the design of the standard operational standards for the implementation of MBKM, the academic collaboration and identification of program support resource needs. This study aims to find out the survey results implementation of the MBKM program at the Faculty of Languages Widyatama University in supporting the vision and mission of the University. In addition, this study purposes to comprehend knowledge related to the MBKM program, the MBKM curriculum and to find out the obstacles encountered during program implementation and relation in shaping the character of students to be professional. The result of this study showed that 99.89% has familiar with MBKM program through the socialization program carried out by university. Besides, the curriculum of MBKM has been implemented at Faculty of Languages in both departments, within the transition phase.